Evaluating the Quality of Selected Spring Waters in Singosari and Karangploso District Using Phytoplankton as Bioindicators - Gumilang, Retno; Hakim, Luchman; Retnaningdyah, Catur (Biotropika: Journal of Tropical Biology, 2025)
The integrity of the water quality in the ecosystem must be maintained to provide benefits for the environment and the living creatures within it. The Singosari and Karangploso Districts have many springs which are usually used by the local community for various needs. Water quality can be evaluated using several types of bioindicators, and phytoplankton is one of the reliable bioindicators. This research aims to evaluate the water quality in Suceng, Nyolo, Sumberawan, Umbulan Ngenep, Nagan, Biru, Belik, Suko, and Umbulan Springs in Singosari using phytoplankton as a bioindicator. The research was conducted from June to September 2024. The physical and chemical parameters observed in the water were air temperature, water temperature, conductivity, total suspended solids (TSS), nitrate, orthophosphate, dissolved oxygen (DO), and biochemical oxygen demand (BOD). Determination of the phytoplankton community structure profile was carried out by calculating taxa richness/TR, IVI, H', dominance index/ID, %PTV, and TDI. The results showed that all physical and chemical quality parameters have met the Indonesian government’s Class II standards.  The phytoplankton H’ values range between 3.39 and 4.32, indicating the water is uncontaminated by toxic materials. However, based on %PTV, Belik Spring is considered heavily organic polluted water (%PTV 70), and Umbulan Ngenep is classified as moderately organic polluted water (39%). Based on TDI measurement, it can be concluded that Nyolo, Suceng, Sumberawan, Suko, and Umbulan Spring were considered as oligoeutrophic (TDI 12.0-25.0), while Nagan, Biru, Umbulan Ngenep, and Belik were classified as mesoeutrophic water (TDI 25.7-45.3). Therefore, it is essential to control the human activities around the springs in Karangploso and Singosari.